FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Sunarsih, Ni Made; Kumarantini, Ni Wayan Rian (Jurnal Riset Akuntansi (JUARA), 2018)
Disclosure of social responsibility or Corporate Social Responsibility (CSR) of a company is influenced by the financial performance of a company. The purpose of this study is to determine the effect of financial performance and Firm Size on CSR. This study uses data on property and real estate companies listed on the Indonesia Stock Exchange 2013-2016. Sample in this research is 23 company with amount of observation 92 data. Data analysis technique used in this research is multiple regression analysis.The result of hypothesis testing shows that the variable of Current Ratio, Debt to Equity Ratiodan Net Profit Margin has no effect on CSR disclosure. As for variable Total Asset Turnover and Firm Size have positive effect to CSR.